Supernumerary chromosomes, Robertsonian rearrangement and multiple NORs in Corydoras aeneus (Pisces, Siluriformes, Callichthyidae) - Oliveira, C.; Toledo, L. F. Almeida; Foresti, F. [UNESP]; Toledo, S. A. (Firenze University Press, 1988)
Cytogenetic studies in four samples of Corydoras aetteus from tributaries of the Tietê River in the upper Paraná System, Brazil (rivers Araquá, Corumbataí, Capivara and Alambari) evidenced a diploid number of 2n = 60 and 2n = 61 plus a variable number of 0 to 3 small supernumeraries or B chromosomes. The variability in the A complement was due to the occurrence of a Robertsonian rearrangement. The supernumerary chromosomes were almost totally C-band positive. The analysis of male meiotic cells showed the occurrence of 29 bivalents and one trivalent in the individuals heterozygous for the Robertsonian rearrangement and of univalents in the individuals with supernumerary chromosomes. Four chromosome pairs are involved in nucleolar organization. All the 4 samples presented supernumerary chromosomes, but the Robertsonian rearrangement was restricted to the rivers Araqua and Corumbataí. © 1988 by the Japan Society for Bioscience, Biotechnology, and Agrochemistry.